Implementation Of Sharia Principles in Financial Technology: Analysis of Regulatory Compliance and Legal Challenges in Indonesia - Herawan, Jajang; Fautanu, Idzam; Janwari, Yadi; Al Hakim, Sofian (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
The rapid growth of financial technology (fintech) in Indonesia has intensified the need to ensure compliance with Sharia principles within digital financial services. This study examines the extent of regulatory compliance of Sharia fintech in Indonesia and identifies the main legal and operational challenges in implementing Islamic economic law. Using a qualitative normative approach based on regulatory analysis and literature review, this research analyzes OJK regulations, DSN-MUI fatwas, and the operational practices of Sharia fintech platforms. The findings reveal that despite the availability of a formal regulatory framework, the implementation of Sharia principles remains uneven. Significant gaps are identified in transparency of profit-sharing mechanisms, Sharia-based risk management, and the effectiveness of supervision by Sharia supervisory bodies. In addition, inconsistencies between regulatory provisions and operational interpretations contribute to varying levels of Sharia compliance among fintech platforms. These findings imply the need for stronger regulatory coordination between OJK and DSN-MUI, clearer technical guidelines for Sharia contract implementation in digital platforms, and the enhancement of supervisory mechanisms to ensure consistent Sharia compliance. Strengthening these aspects is essential to support the sustainable development of Sharia fintech and to enhance public trust in Indonesia’s digital Islamic financial ecosystem.